The Canadian journal of economics. Revue canadienne d'e?conomique. - Canadian Economics Association (Toronto Published for the Canadian Economics Association by the University of Toronto Press.)
Carries significant contributions to knowledge in all areas of economics. Papers and reviews are in French and English.
Keywords: Economics -- Periodicals